Febuxostat combined with hydration for the prevention of contrast-induced nephropathy in hyperuricemia patients undergoing percutaneous coronary intervention: A CONSORT-compliant randomized controlled trial. Issue 4 (28th January 2022) - Ma, Guang; Li, Min; Teng, Wei; He, Zhaohui; Zhai, Xiaojv; Xia, Zhenhua
Abstract: Background: To assess the efficacy of febuxostat combined with hydration on contrast-induced nephropathy (CIN) in coronary heart disease patients with hyperuricemia undergoing percutaneous coronary intervention (PCI). Methods: Patients with hyperuricemia who underwent PCI were randomly assigned to 2 groups. The control group was given hydration only, and the febuxostat group received febuxostat 40 mg daily before administration of contrast agent and hydration. The primary endpoint of the study was the incidence of CIN, defined as an increase in baseline serum creatinine concentration by 25% at 2 days after contrast media administration, and variations in the serum levels of creatinine, neutrophil gelatinase-associated lipocalin, uric acid, and estimated glomerular filtration rate were compared. Results: A total of 202 patients with hyperuricemia were randomly assigned to either the febuxostat group (n = 100) or the control group (n = 102). The baseline characteristics of the 2 groups were similar. The incidence of CIN was 6.0% (6/100) in the febuxostat group and 14.71% (15/102) in the control group. The levels of neutrophil gelatinase-associated lipocalin at 6-hour and serum creatinine and uric acid at 48-hour in the febuxostat combined hydration group were lower than those in the control group after surgery, and the level of estimated glomerular filtration rate was higher than that in the control group (all P < .05). Multivariate logistic regression analysis revealed that febuxostat was an independent predictor of CIN. Conclusion: Our study demonstrated that prophylactic treatment with febuxostat combined with hydration can reduce the incidence of CIN in patients with coronary heart disease and hyperuricemia after PCI.